2016
DOI: 10.1002/cam4.847
|View full text |Cite
|
Sign up to set email alerts
|

ZNF703 Overexpression may act as an oncogene in non‐small cell lung cancer

Abstract: Despite therapeutic advances, lung cancer remains one of the most common causes of cancer‐related deaths worldwide. The ZNF703 gene has been identified as the driver of the 8p11‐12 region and its amplification or overexpression has been associated with several types of cancers. It has also been shown that ZNF703 overexpression can activate the Akt/mTOR signaling pathway. The aim of our study was to investigate the role of the ZNF703 gene in association with Akt/mTOR activation in non‐small cell lung cancer (NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 36 publications
5
25
0
Order By: Relevance
“…In this study , we found that the loss of ZNF703 expression decreased the expression of p-PI3K, p-Akt, and p-GSK-3β. These results are similar to the findings of the study by Baykara et al in which ZNF703 was shown to contribute to tumour development in NSCLC by activating the Akt/mTOR pathway [12]. To specifically determine the effects of PI3K and Akt on the ZNF703-mediated promotion of cell proliferation and metastasis, we father employed the Akt inhibitor MK2206 and the PI3K inhibitor LY294002 to inhibit the expression of Akt and PI3K, respectively, in ZNF703-upregulated cells.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In this study , we found that the loss of ZNF703 expression decreased the expression of p-PI3K, p-Akt, and p-GSK-3β. These results are similar to the findings of the study by Baykara et al in which ZNF703 was shown to contribute to tumour development in NSCLC by activating the Akt/mTOR pathway [12]. To specifically determine the effects of PI3K and Akt on the ZNF703-mediated promotion of cell proliferation and metastasis, we father employed the Akt inhibitor MK2206 and the PI3K inhibitor LY294002 to inhibit the expression of Akt and PI3K, respectively, in ZNF703-upregulated cells.…”
Section: Discussionsupporting
confidence: 88%
“…The overexpression of ZNF703 is thought to play an important role in various human cancers [12, 13, 15, 23]; however, the role and molecular mechanism if ZNF703 are not well understood in OSCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Baykara et al. data also show that ZNF703 may contribute to tumor development in NSCLC by activating the Akt/mTOR pathway. Additionally, Ma et al.…”
Section: Discussionmentioning
confidence: 86%